Detection of low copy number integrated viral DNA formed by in vitro Hepatitis B infection - Tu, Thomas; Urban, Stephan (JoVE. Video journal, 2018)
Hepatitis B Virus (HBV) is a common blood-borne pathogen causing liver cancer and liver cirrhosis resulting from chronic infection. The virus generally replicates through an episomal DNA intermediate; however, integration of HBV DNA fragments into the host genome has been observed, even though this form is not necessary for viral replication. The exact purpose, timing, and mechanism(s) by which HBV DNA integration occurs is not yet clear, but recent data show that it occurs very early after infection. Here, the in vitro generation and detection of HBV DNA integrations are described in detail. Our protocol specifically amplifies single copies of virus-cell DNA integrations and allows both absolute quantification and single-base pair resolution of the junction sequence. This technique has been applied to various HBV-susceptible cell types (including primary human hepatocytes), to various HBV mutants, and in conjunction with various drug exposures. We foresee this technique becoming a key assay to determine the underlying molecular mechanisms of this clinically relevant phenomenon.